1992
DOI: 10.1002/ajim.4700210209
|View full text |Cite
|
Sign up to set email alerts
|

Occupational lead exposure in Los Angeles county: An occupational risk surveillance strategy

Abstract: To better understand occupational lead exposures in Los Angeles County, we undertook a questionnaire survey of lead-using industrial facilities not previously identified by county health department staff. Previously our staff had identified 112 lead-using companies with approximately 2,000 lead-exposed workers countywide. For this survey, we developed a database of 1,353 possible lead-using industrial facilities from several sources, including community "right-to-know" databases, air pollution or sewer permit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…2003;45:724 -733) L ead poisoning in radiator repair workers and their families is welldocumented. [1][2][3][4][5][6][7][8][9][10] Studies of radiator repair workers in California 2 and Colorado 11 revealed that 60% and 62%, of workers, respectively, had blood lead levels (BLLs) Ͼ25 g/ dL. Radiator mechanics are exposed to airborne lead fumes when they disassemble radiators by melting solder joints using torches heated to at least 260°C (500°F).…”
Section: Stephen G Whittaker Phdmentioning
confidence: 99%
“…2003;45:724 -733) L ead poisoning in radiator repair workers and their families is welldocumented. [1][2][3][4][5][6][7][8][9][10] Studies of radiator repair workers in California 2 and Colorado 11 revealed that 60% and 62%, of workers, respectively, had blood lead levels (BLLs) Ͼ25 g/ dL. Radiator mechanics are exposed to airborne lead fumes when they disassemble radiators by melting solder joints using torches heated to at least 260°C (500°F).…”
Section: Stephen G Whittaker Phdmentioning
confidence: 99%
“…12 Exposure reduction has long been recognized as the principal means of prevention. Although the US Occupational Safety and Health Administration (OSHA) adopted comprehensive lead regulations in 1978, 3 occupational lead poisoning remains a serious and persistent public health problem.4 '5 From 1987 to 1990, the California Occupational Lead Registry-a laboratorybased surveillance system-received reports of 1503 adults with blood lead levels of 1.93 ,umol/L (40 ,ug/dL) or higher.6 '7 The true number of workers with blood lead above that level may be much higher, because only a small fraction of lead-exposed workers receive routine blood lead testing.8 Other workers are likely to be untested and thus unreported even if they have seriously elevated blood lead levels.…”
Section: Introductionmentioning
confidence: 99%
“…Except in specific areas or targeted industries, as in Los Angeles County and New York City [Papanek et al, 1992;Bellows and Rudolph, 1993;Nunez et a]., 19931, few efforts have been reported of extensive educational efforts targeted at groups of employers identified through surveillance systems, with a goal of achieving reduced lead exposures.…”
Section: Targeted Educational Activitiesmentioning
confidence: 97%
“…The health care provider should be required to provide all necessary information to the laboratory as a responsibility of supervising a biological monitoring program. [Papanek et al, 1992;Bellows and Rudolph, 1993;Nunez et al, 19931. The Occupational Safety and Health Administration (OSHA) has recently closed one of the major gaps in the regulatory control of lead poisoning by promulgating a standard of lead exposure in the construction trades [OSHA, 19931. However, an integrated approach to preventing occupational lead poisoning and overexposure nationwide has not been proposed.…”
Section: Introductionmentioning
confidence: 96%